2018
DOI: 10.11646/phytotaxa.365.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Revision of the Synechococcales (Cyanobacteria) through recognition of four families including Oculatellaceae fam. nov. and Trichocoleaceae fam. nov. and six new genera containing 14 species

Abstract: A total of 48 strains of thin, filamentous cyanobacteria in Synechococcales were studied by sequencing 16S rRNA and rpoC1 sequence fragments. We also carefully characterized a subset of these by morphology. Phylogenetic analysis of the 16S rRNA gene data using Bayesian inference of a large Synechococcales alignment (345 OTU’s) was in agreement with the phylogeny based on the rpoC1 gene for 59 OTU’s. Both indicated that the large family-level grouping formerly classified as the Leptolyngbyaceae could be further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
200
0
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(229 citation statements)
references
References 38 publications
18
200
0
11
Order By: Relevance
“…, Mai et al. ). It is possibly ironic that we are the ones to propose that the partitioning of the cyanobacterial genus Desertifilum into four cryptic species has gone too far.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…, Mai et al. ). It is possibly ironic that we are the ones to propose that the partitioning of the cyanobacterial genus Desertifilum into four cryptic species has gone too far.…”
Section: Discussionmentioning
confidence: 99%
“…, Mai et al. ). The increase in use of 16S rRNA gene sequence data in combination with the characterization of the secondary structure of ribosomal internal transcribed spacer regions (16S–23S ITS) has been found to be important in delimitation of genera and species (Perkerson et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…, Mai et al. ), sequences assigned to several Leptolyngbya morphospecies still place outside Leptolyngbya sensu stricto (Osorio‐Santos et al. , Becerra‐Absalon et al.…”
mentioning
confidence: 99%
“…Molecular evaluation is required for most of the baeocyte producers within Pleurocapsales because of the cryptic features of some taxa. The presence of cryptic species and genera (Kom arek et al 2014, Kom arek 2018 has been identified in members of the Synechococcales (Osorio-Santos et al 2014, Mai et al 2018, Nostocales (Bohunick a et al 2015, Shalygin et al 2017, Gonz alez-Resendiz et al 2018, and Oscillatoriales (Boyer et al 2002, Caires et al 2018 and we suspect cryptic taxa may be more widespread in baeocyte producing forms from order Pleurocapsales than currently known. Herein we describe a new genus and species, Odorella benthonica, following the monophyletic species concept sensu Johansen and Casamatta (2005), with biochemical profiling as done previously (Zimba et al 2017).…”
mentioning
confidence: 67%